Governing Rural Finance: The Mediating Role of Fraud Prevention on Moslem Community Welfare - Sartiyah, Sartiyah; Yusrizal, Yusrizal; Suriani, Suriani; Usman, Musliadi bin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study investigates the mediating role of fraud prevention in the relationship between human capital, village financial planning, and moslem community welfare. Focusing on 260 villages in South Aceh, a sample of 120 respondents from 40 randomly selected village fund recipients was surveyed, comprising village financial staff, development planning staff, and members of the Village Council (Tuha Peut). The study employs the Structural Equation Modeling–Partial Least Squares (SEM–PLS) approach, with bootstrapping techniques used to assess mediation effects. The findings indicate that the quality of human resources directly influences both community welfare and fraud prevention. However, fraud prevention does not significantly mediate the relationship between human resource quality and community welfare. Conversely, it plays a significant mediating role in the relationship between village financial planning and community welfare. These results underscore the strategic importance of implementing robust fraud prevention mechanisms within financial planning processes to enhance moslem community welfare. The study recommends prioritizing fraud prevention initiatives alongside human capital development to maximize the impact of village fund programs on moslem welfare outcomes.========================================================================================================ABSTRAK - Tata Kelola Dana Desa: Peran Mediasi Pencegahan Kecurangan terhadap Kesejahteraan Masyarakat Muslim. Penelitian ini mengkaji peran mediasi pencegahan kecurangan dalam hubungan antara kualitas sumber daya manusia, perencanaan keuangan desa, dengan kesejahteraan masyarakat muslim. Kajian ini terfokus pada 260 desa di Aceh Selatan, dengan sampel terdiri dari 120 responden dari 40 desa penerima dana desa yang dipilih secara acak, yaitu staf keuangan desa, staf perencanaan pembangunan, dan anggota Tuha Peut (dewan penasehat desa). Penelitian ini menggunakan pendekatan Structural Equation Modeling–Partial Least Squares (SEM–PLS), dengan teknik bootstrapping untuk menguji efek mediasi. Hasil penelitian menunjukkan bahwa kualitas sumber daya manusia secara langsung berpengaruh terhadap kesejahteraan masyarakat dan pencegahan kecurangan. Namun, pencegahan kecurangan tidak memediasi secara signifikan hubungan antara kualitas sumber daya manusia dan kesejahteraan masyarakat. Sebaliknya, pencegahan kecurangan memediasi secara signifikan hubungan antara perencanaan keuangan desa dan kesejahteraan masyarakat. Temuan ini menegaskan pentingnya penerapan mekanisme pencegahan kecurangan yang kuat dalam proses perencanaan keuangan untuk meningkatkan kesejahteraan dalam konteks masyarakat muslim. Penelitian ini merekomendasikan agar upaya pencegahan kecurangan dan pengembangan sumber daya manusia menjadi prioritas dalam program dana desa guna mengoptimalkan dampaknya terhadap kesejahteraan masyarakat muslim.